Design of dual band four port circularly polarized MIMO DRA for WLAN/WiMAX applications. Issue 15 (12th October 2020) - Dwivedi, Ajay Kumar; Sharma, Anand; Singh, Ashutosh Kumar; Singh, Vivek
Abstract : This article presents a circularly polarized 4-port Multiple Inputs Multiple Outputs dielectric resonator-based antenna with two resonating bands for WLAN (5.0 GHz) and WiMAX (3.5 GHz) applications. Important attributes of proposed MIMO-DRA are: (i) Bandwidth enhancement is observed due to the use of ring-shaped ceramic material radiator; (ii) Incorporation of rectangular aperture lead to excite the dual hybrid mode in ring DRA, which helps to support dual-frequency range (iii) Circular polarization is achieved in both operating bands by conversion of rectangular to Z-shaped slot; and (iv) mutual coupling among port <−18 dB due to the use of space diversity. The fabricated prototype of the MIMO radiator is measured experimentally, which confirms the dual impedance bandwidth of 3.35 – 3.82 GHz and 5.09 – 5.41 GHz. The proposed antenna is right-handed circularly polarized (RHCP) within the frequency range of 3.54 – 3.72 GHz & 5.04 – 5.16 GHz respectively.